Role of abdominal obesity for functional outcomes and complications in men treated with radical prostatectomy for prostate cancer: results of the Multicenter Italian Report on Radical Prostatectomy (MIRROR) study. (April 2014) - Gacci, Mauro; Sebastianelli, Arcangelo; Salvi, Matteo; De nunzio, Cosimo; Schiavina, Riccardo; Simonato, Alchiede; Tubaro, Andrea; Mirone, Vincenzo; Carini, Marco; Carmignani, Giorgio
Abstract Objective. This study aimed to evaluate the impact of abdominal obesity on preoperative features, complications and functional outcomes of men treated with radical prostatectomy (RP) for prostate cancer. Material and methods. In 2006 a multicentre Italian report on RP evaluated the surgical and functional characteristics of prostate cancer and RP outcomes. Age and waist circumference (WC) were recorded. Abdominal obesity was defined as a WC of at least 102 cm. International Index of Erectile Function (IIEF) score, prostate-specific antigen, prostate volume, tumour characteristics, presence/absence of perioperative complications and the number of blood units transfused were recorded. Preoperative and postoperative continence status was evaluated. Spearman correlation coefficient and binary logistic regression analyses were conducted. Results. In total, 470 men were recruited. A significant negative correlation between WC and preoperative IIEF scores was observed (r = –0.032, p < 0.001). Non-obese patients presented a preoperative IIEF score of 18.8 ± 6.0 and obese patients an IIEF score of 16.0 ± 7.0 (p < 0.001). Obese men are at three-fold greater risk of intraoperative complications and blood transfusions than those with a WC below 102 cm [adjusted odds ratio (OR) = 3.116, 95% confidence interval (CI) 0.281–16.348, p < 0.001, and OR = 2.763, 95% CI 0.518–3.843, p < 0.050, respectively]. A significant positive correlation between WC and postprostatectomy incontinence severity was observed. The risk of needing at least two pads per day is two and a half times greater in men with a WC of at least 102 cm than in those with a WC below 102 cm (adjusted OR = 2.435, 95% CI 0.321–7.668, p = 0.007). Conclusion. Abdominal obesity in a multicentre Italian cohort of patients treated with RP was associated with an increased risk of intraoperative and perioperative complications and with a worse functional outcome.